Evaluation of SEPT2 and SEPT4 transcript contents in spermatozoa from men with asthenozoospermia and teratozoospermia. Issue 4 (23rd November 2021) - Mazaheri Moghaddam, Madiheh; Mazaheri Moghaddam, Marziyeh; Amini, Mohammad; Bahramzadeh, Behzad; Baghbanzadeh, Amir; Biglari, Alireza; Sakhinia, Ebrahim
Abstract: Background and aims: Motility and morphological defects of spermatozoa can cause male infertility. Sperm RNAs are related to sperm quality. They are considered to have clinical values as a biomarker for assessing sperm quality and fertility potential. The annulus, located in the mammalian sperm tail, is required for motility and terminal differentiation of the spermatozoa. SEPT2, 4, 6, 7, and 12 proteins are the main components of the annulus in the sperm tail. The study aimed to evaluate SEPT2 and SEPT4 mRNA contents in the spermatozoa of patients with asthenozoospermia and teratozoospermia. Methods: We evaluated transcript levels of SEPT2 and SEPT4 in the sperm samples of 20 asthenozoospermic, 20 teratozoospermic, and 20 normozoospermic samples using quantitative PCR. Results: The SEPT2 transcript level was significantly decreased in the asthenozoospermia samples compared with the normal group ( P = .013). However, SEPT4 was not significantly different between these two groups. The transcript levels of SEPT2 and SEPT4 were not statistically different between teratozoospermic and normozoospermic groups. Conclusion: In conclusion, downregulation of SEPT2 in patients with asthenozoospermia appears to be associated with poor sperm motility.